HUMPBACK DOLPHIN SOUSA CHINENSIS IN CAPTIVITY - Lalmohan, R S (Indian Journal of Fisheries, 2011)
A dolphin Sousa chinensis mfiasuring 2.3 m was accidentally got entangledin a gill net set oiT Calicut on 12-2-1981. Subsequently, it'was released ina polythene lined pond, 20 x IQ x'1.5 m, filled with sea water. The water temperatureof the pond ranged from 27Â°C to 31Â°C